Holstein and Jersey Steers Differ in Rumen Microbiota and Enteric Methane Emissions Even Fed the Same Total Mixed Ration - Islam, Mahfuzul; Kim, Seon-Ho; Ramos, Sonny C.; Mamuad, Lovelia L.; Son, A-Rang; Yu, Zhongtang; Lee, Sung-Sil; Cho, Yong-Il; Lee, Sang-Suk (Frontiers in Microbiology, 2021)
Previous studies have focused on the rumen microbiome and enteric methane (CH4) emissions in dairy cows, yet little is known about steers, especially steers of dairy breeds. In the present study, we comparatively examined the rumen microbiota, fermentation characteristics, and CH4 emissions from six non-cannulated Holstein (710.33 ± 43.02kg) and six Jersey (559.67 ± 32.72kg) steers. The steers were fed the same total mixed ration (TMR) for 30 days. After 25 days of adaptation to the diet, CH4 emissions were measured using GreenFeed for three consecutive days, and rumen fluid samples were collected on last day using stomach tubing before feeding (0 h) and 6 h after feeding. CH4 production (g/d/animal), CH4 yield (g/kg DMI), and CH4 intensity (g/kg BW0.75) were higher in the Jersey steers than in the Holstein steers. The lowest pH value was recorded at 6 h after feeding. The Jersey steers had lower rumen pH and a higher concentration of ammonia-nitrogen (NH3-N). The Jersey steers had a numerically higher molar proportion of acetate than the Holstein steers, but the opposite was true for that of propionate. Metataxonomic analysis of the rumen microbiota showed that the two breeds had similar species richness, Shannon, and inverse Simpson diversity indexes. Principal coordinates analysis showed that the overall rumen microbiota was different between the two breeds. Both breeds were dominated by Prevotella ruminicola, and its highest relative abundance was observed 6 h after feeding. The genus Ethanoligenens, Succinivibrio, and the species E. harbinense, S. dextrinosolvens, Pr. micans, Pr. copri, Pr. oris, Pr. baroniae, and T. succinifaciens were more abundant in Holstein steers while the genus Capnocytophaga, Lachnoclostridium, Barnesiella, Oscillibacter, Galbibacter, and the species Ca. cynodegmi, G. mesophilus, B. intestinihominis, Pr. Shahii, and O. ruminantium in the Jersey steers. The Jersey steers were dominated by Methanobrevibacter millerae while the Holstein steers by M. olleyae. The overall results suggest that sampling hour has little influence on the rumen microbiota; however, breeds of steers can affect the assemblage of the rumen microbiota and different mitigation strategies may be needed to effectively manipulate the rumen microbiota and mitigate enteric CH4 emissions from these steers.